Fluorescent‐Ligand‐Mediated Screening of G‐Quadruplex Structures Using a DNA Microarray1. Issue 46 (21st October 2013) - Iida, Keisuke; Nakamura, Takahiro; Yoshida, Wataru; Tera, Masayuki; Nakabayashi, Kazuhiko; Hata, Kenichiro; Ikebukuro, Kazunori; Nagasawa, Kazuo
<x xml:space="preserve">Abstract</x> Light up, G‐quadruplexes! A fast high‐throughput screening for the discovery of novel G‐quadruplex‐forming oligonucleotides (GFOs) has been developed. By using a fluorescent G‐quadruplex ligand and a DNA microarray, 1998 novel GFO candidates in CpG islands were disclosed. (CpG=cytosine‐phosphate‐guanosine).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>